The 239Pu nuclear fallout as recorded in an Antarctic ice core drilled at Dome C (East Antarctica). (July 2023) - Severi, Mirko; Becagli, Silvia; Caiazzo, Laura; Nardin, Raffaello; Toccafondi, Alberto; Traversi, Rita
Abstract: Starting from 1952 C.E. more than 540 atmospheric nuclear weapons tests (NWT) were conducted in different locations of the Earth. This lead to the injection of about 2.8 t of 239 Pu in the environment, roughly corresponding to a total 239 Pu radioactivity of 6.5 PBq. A semiquantitative ICP-MS method was used to measure this isotope in an ice core drilled in Dome C (East Antarctica). The age scale for the ice core studied in this work was built by searching for well-known volcanic signatures and synchronising these sulfate spikes with established ice core chronologies. The reconstructed plutonium deposition history was compared with previously published NWT records, pointing out an overall agreement. The geographical location of the tests was found to be an important parameter strongly affecting the concentration of 239 Pu on the Antarctic ice sheet. Despite the low yield of the tests conducted in the 1970s, we highlight their important role in the deposition of radioactivity in Antarctica due to the relative closeness of the testing sites. Graphical abstract: Image 1 Highlights: Nuclear Weapons Tests were responsible of a global dispersion of radioactivity. Antarctic ice-cores preserve a detailed record of nuclear fallout. An ICP-MS method was successfully used to measure 239 Pu at fg g −1 level. The nuclear fallout can represent an useful tool for the dating of an ice-core.